Analyzing and Interpreting Lime Burials from the Spanish Civil War (1936–1939): A Case Study from La Carcavilla Cemetery1. Issue 2 (1st December 2016) - Schotsmans, Eline M. J.; García‐Rubio, Almudena; Edwards, Howell G. M.; Munshi, Tasnim; Wilson, Andrew S.; Ríos, Luis
Abstract: Over 500 victims of the Spanish Civil War (1936–1939) were buried in the cemetery of La Carcavilla (Palencia, Spain). White material, observed in several burials, was analyzed with Raman spectroscopy and powder XRD, and confirmed to be lime. Archaeological findings at La Carcavilla's cemetery show that the application of lime was used in an organized way, mostly associated with coffinless interments of victims of Francoist repression. In burials with a lime cast, observations made it possible to draw conclusions regarding the presence of soft tissue at the moment of deposition, the sequence of events, and the presence of clothing and other evidence. This study illustrates the importance of analyzing a burial within the depositional environment and taphonomic context.